2012
DOI: 10.21273/hortsci.47.7.821
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Crops of Asia and Southeast Asia: Exploring Health-promoting Properties

Abstract: Diets rich in vegetables and fruits are known to be protective against several diseases. Only a limited number of vegetables and fruits are consumed as part of the daily diet in Western countries. Historically, indigenous vegetables and fruits are known for their medicinal and nutritional value in countries where they were originated and/or domesticated. However, relatively few systemic studies and reviews were conducted to enumerate the potential of these vegetables to human health benefits. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…Plant uniformity and vigor were both assessed on a 1-5 scale, which is visually described as 1 = poor, 2 = marginal, 3 = fair, 4 = good, and 5 = excellent. Since some indigenous Asian cultivars have been shown to provide potential health-promoting properties and have Asian popularity (Molinar, 2012;Patel et al, 2012), especially in the Curcurbitaceae, Fabaceae, Gramineae, Solanaceae, and Cruciferae, a preliminary analysis was conducted for phytochemical composition of a few promising cultivars in east coast trials.…”
Section: Methodsmentioning
confidence: 99%
“…Plant uniformity and vigor were both assessed on a 1-5 scale, which is visually described as 1 = poor, 2 = marginal, 3 = fair, 4 = good, and 5 = excellent. Since some indigenous Asian cultivars have been shown to provide potential health-promoting properties and have Asian popularity (Molinar, 2012;Patel et al, 2012), especially in the Curcurbitaceae, Fabaceae, Gramineae, Solanaceae, and Cruciferae, a preliminary analysis was conducted for phytochemical composition of a few promising cultivars in east coast trials.…”
Section: Methodsmentioning
confidence: 99%
“…Snake gourd is also considered to be useful in treating type 2 diabetes [209]. Ridge gourd contains insulin like peptides, and alkaloids that help to lower fasting blood glucose levels [209] [217].…”
Section: Effect On Diabetesmentioning
confidence: 99%
“…Bitter gourd (Momordica charantia) has been intensively studied for its antidiabetic attributes. Different studies reported hypoglycemic and antihyperglycemic properties of bitter gourd [209,[216][217][218]. Clinical surveys on diabetic patients using pulp and juice extracts of bitter gourd were reported to bring down serum insulin levels, to lower fasting blood glucose levels, and to ameliorate glucose tolerance [219].…”
Section: Effect On Diabetesmentioning
confidence: 99%